Hamilton, Clive (2017) Defiant Earth - The Fate of Humans in the Anthropocene - Milhano, Ângelo (Anthropocenica. Journal of Anthropocene Studies and Ecocriticism, 2023)
Recensão crítica da obra: Hamilton, Clive (2017) Defiant Earth - The Fate of Humans in the Anthropocene.